THE ROLE OF PRECEDENTS AS A FILTER FOR ARGUMENTATION - Perrone Campos Mello, Patrícia (REVISTA DA AGU, 2016)
This essay examines the role and the limits of a theory of precedent in promoting the values of legal certainty, equality, legitimacy, and efficiency of the courts. It demonstrates, further, that precedents have another major role: they serve as a filter for legal argumentation, guiding litigants and judges on the issues to be discussed and considered in the decision of a case. With this objective, section I clarifies the relationship between the use of precedents and the values mentioned above. Section II demonstrates the manner in which precedents are applied. Section III analyses the subjective and institutional elements that also influence judicial behavior. Finally, section IV presents the conclusion, highlighting the importance of precedents for legal reasoning.